2016
DOI: 10.1016/j.ajpath.2015.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Mast Cell-Derived Histamine Decreases Human Cholangiocarcinoma Growth and Differentiation via c-Kit/Stem Cell Factor–Dependent Signaling

Abstract: The tumor microenvironment of cholangiocarcinoma (CCA) is composed of numerous cells, including mast cells (MCs). MCs release histamine, which increases CCA progression and angiogenesis. Cholangiocytes secrete stem cell factor, which functions via the MC growth factor receptor c-Kit. Here, we show that cholangiocytes express histidine decarboxylase and its inhibition reduces CCA growth. MC recruitment in the tumor microenvironment increased CCA growth. MC infiltration and MC markers were detected by toluidine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
102
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 63 publications
(109 citation statements)
references
References 38 publications
7
102
0
Order By: Relevance
“…Inhibition of mast cell-derived histamine prevents EMT switch and ECM breakdown in CCA cells through H1HR and H2HR [141]. Moreover, if the SCF/Kit pathway involved in tumor mast cell recruitment is inhibited, the paracrine influence of mast cells on CCA is vanished [141], suggesting a role of mast cells/tumor cells interaction in the promotion of EMT and progression of CCA.…”
Section: Tumor-associated Macrophages (Tams) and Mast Cells (Figure 3b)mentioning
confidence: 97%
“…Inhibition of mast cell-derived histamine prevents EMT switch and ECM breakdown in CCA cells through H1HR and H2HR [141]. Moreover, if the SCF/Kit pathway involved in tumor mast cell recruitment is inhibited, the paracrine influence of mast cells on CCA is vanished [141], suggesting a role of mast cells/tumor cells interaction in the promotion of EMT and progression of CCA.…”
Section: Tumor-associated Macrophages (Tams) and Mast Cells (Figure 3b)mentioning
confidence: 97%
“…Prior to isolation of mast cells, we performed toluidine blue staining and staining in livers from normal rats and BDL rats (6 hr to 14 days post BDL) to verify the presence and localization of hepatic mast cells(12, 14). To perform toluidine blue staining, paraffin-embedded livers were sliced (4–5 μm) and deparaffanized prior to toluidine blue staining.…”
Section: Methodsmentioning
confidence: 99%
“…Traditionally, mast cell activation occurs via typical IgE/FCεRI receptor binding, however mast cells can also be triggered by the activation of the numerous ligands and G-protein coupled receptors found on their surface including histamine receptors (H1–H4)(10, 11). We have recently demonstrated that mast cell activation and chemoattraction occurs via a stem cell factor/c-kit interaction during cholangiocarcinoma progression(12). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gabexate mesylate, nafamostat mesylate, and tranilast are mast cells inhibitors recently studied as new promising antiangiogenic agents (Ammendola et al 2014). Disodium cromolyn, another mast cell stabilizer, has a widely accepted antitumor effects in several tumor types as cholangiocarcinoma (Johnson et al 2016), pancreatic cancer (Kim et al 2012) or breast malignancies (Samoszuk and Corwin 2003). All effects of mast cell stabilizers described above are related with mast cells inhibition.…”
Section: Introductionmentioning
confidence: 99%